Knowledge and Uptake of VIA Screening: A Case-Control Study among Women of Reproductive Age in Kendari City - Julian Jingsung (Jurnal Bidan Cerdas, 2025)
Background: Cervical cancer remains one of the leading causes of mortality among women in Indonesia, largely due to low uptake of early detection methods such as Visual Inspection with Acetic Acid (VIA) screening. Knowledge among women of reproductive age (WRA) has been identified as an important factor associated with participation in screening. This study aimed to examine the association between knowledge level of WRA and VIA screening uptake at the BLUD UPTD Wua-Wua Public Health Center in Kendari City. Methods: A case-control design was applied involving 64 respondents, comprising 32 cases (women who had undergone VIA screening) and 32 controls (women who had not). Cases and controls were determined based on service records from the health center. Data were collected from June to August 2024 using a structured and validated questionnaire. The Chi-Square test was used for statistical analysis with a significance level of 0.05. Results: More than half of respondents (54.7%) demonstrated low knowledge. A significant association was found between knowledge level and VIA screening uptake (p<0.001). Conclusion: Knowledge level was significantly associated with VIA screening behavior among WRA. These findings suggest that strengthening awareness and educational efforts may contribute to improving participation in cervical cancer early detection programs.